Pengembangan Modul Pembelajaran Pemesinan Bubut Berbasis E-Literacy Pada Mata Pelajaran Teknik Pemesinan Bubut - Priyas Tri Bandi; Rabiman Rabiman; Arif Bintoro Johan (JURNAL VOKASI DEWANTARA (JVD), 2023)
This study aims to: (1) create a learning module for Lathe Machining Engineering; and (2) analyze the feasibility of the lathe machining engineering module by experts. The type of research is development research (R&D). The research subjects were students of class XI SMK Nasional Berbah, while the object of the research was the e-literacy-based lathe-machining technique module. The instrument of this research was a questionnaire to provide a feasibility assessment of the lathe engineering module by material experts, media experts, subject teachers and students. The data analysis technique used descriptive statistical analysis. The results showed that the feasibility of the lathe engineering subject module from the analysis of the assessment results of the material expert lecturers I obtained an average of 3.46 in the "Very Good" classification, from the results of the II material expert assessments, an average of 3.58 was found in the "Very Good" classification, from the results of the assessment of media expert lecturers, an average of 3.27 was found in the "Very Good" classification. The limited trial obtained an average of 3.35 which is in the "Very Good" classification. The readability test got an average of 3.28 in the "Very Good" classification. It can be concluded that the developed module is suitable for use in learning lathe machining techniques. This research is only limited to the feasibility test of the module, so that for further research it can be further developed the level of effectiveness of the module on the achievement of student competencies.